GERAKAN LITERASI MASYARAKAT KABUPATEN SUMEDANG COMMUNITY LITERACY MOVEMENT OF SUMEDANG REGENCY - Asep Saeful Rohman; Amalia Dewi; Rohanda Rohanda (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2019)
This study discusses the process of formation and pattern of literacy movement activities at Forum Literasi Sumedang (FLS) as a catalyst of literacy based on society movement in human development effort. The purpose of this study is to know how the process of forum formation based on literacy, as well as the pattern of literacy movement activities implemented by the FLS as a catalyst of society movement based on literacy. This research uses qualitative method with case study approach. Technique of collecting data is done by observation, interview, literature study or documentation, and triangulation. The results of this study indicate that the formation of FLS begins with the motive to combine literacy activists to build a network (connection), so the opportunity for the development of literacy movement in Sumedang Regency grew larger. The FLS creation process consists of problem identification, FLS concept formulation, preparation, and launching. The literacy movement activity model at Forum Literasi Sumedang has two patterns, first the FLS as the center or the center of movement, and the second is the FLS as the support system of the initiator community.